Dynamic Thinking Processes in Mathematics Learning: a Systematic Literature Review - Megita Dwi Pamungkas; Stevanus Budi Waluya; Scolastika Mariani; Isnarto Isnarto (Universitas Negeri Semarang, 2022)
Researchers in the field of mathematics education are also growing. This makes research on article reviews very important to do, because it can help researchers in determining the research to be carried out. In this study, a review of research articles on dynamic thinking in mathematics education was carried out. Researchers have investigated dynamic thinking, but what is being studied is diverse. The purpose of this article is to provide an overview of dynamic thinking discussed in mathematics education research. In this study, we analyzed 22 articles published from 1999-2020 with systemtic review. We have searched for articles in the Web of Science database assisted by harzing's publish and perish software with a single keyword or keyword combination. Keywords or combinations of keywords used include dynamic thinking, dynamic of mind, a combination of dynamic thinking and mathematics. We have conducted a systematic review inductively finding dynamic thinking that is discussed in mathematics education. We found that there are still many things that have not been researched by researchers. Researchers are mostly from the United States and Canada. This article also provides an overview of the research of dynamic thought processes whose different focal points are cognitive processes (information processing, abstraction, restructuring, imagination, perceptual decision making), thinking, cognitive abilities, cognition, fMRI, environmental influences, and movement.